2017
DOI: 10.1007/s00426-017-0899-x
|View full text |Cite
|
Sign up to set email alerts
|

Are allocentric spatial reference frames compatible with theories of Enactivism?

Abstract: Theories of Enactivism propose an action-oriented approach to understand human cognition. So far, however, empirical evidence supporting these theories has been sparse. Here, we investigate whether spatial navigation based on allocentric reference frames that are independent of the observer's physical body can be understood within an action-oriented approach. Therefore, we performed three experiments testing the knowledge of the absolute orientation of houses and streets towards north, the relative orientation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(46 citation statements)
references
References 74 publications
6
34
0
Order By: Relevance
“…However, it is challenging to get differential insights into spatial knowledge that was acquired and is used naturally in everyday navigation in a large-scale environment like ones hometown. A previous study (König et al, 2017) investigated allocentric spatial knowledge retrieval after everyday navigation in the hometown of Osnabrück, Germany. They used photographs of houses and streets as stimuli and tested spatial knowledge of the orientation of houses and streets toward cardinal north, the relative orientation of two houses and two streets, respectively, and relative location of two houses in a pointing task.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is challenging to get differential insights into spatial knowledge that was acquired and is used naturally in everyday navigation in a large-scale environment like ones hometown. A previous study (König et al, 2017) investigated allocentric spatial knowledge retrieval after everyday navigation in the hometown of Osnabrück, Germany. They used photographs of houses and streets as stimuli and tested spatial knowledge of the orientation of houses and streets toward cardinal north, the relative orientation of two houses and two streets, respectively, and relative location of two houses in a pointing task.…”
Section: Introductionmentioning
confidence: 99%
“…The opposite pattern was found after map exploration. Previous research, evaluating photographs of real-world houses of the city of Osnabrück after at least one year of living in the city, combining direct experience and cartographic information to get to know the environment (König et al, 2017), found the highest task accuracy in the pointing task as well.…”
Section: Discussionmentioning
confidence: 97%
“…Please note that none of the subjects of the pilot study is included in the main study and that no subjects of the main study were excluded for reasons of their spatial exploration behavior. The instructions were given by written and verbal explanations using photographs of houses in the city of Osnabrück that were used as stimuli in a previous study (König et al, 2017). Participants then performed a pre-task training with one example of each spatial task in both time conditions to gain a better insight into the actual task requirements.…”
Section: Spatial Tasks' Instructions and Tasks' Trainingmentioning
confidence: 99%
See 2 more Smart Citations